Velopharyngeal Inadequacy-Related Quality of Life Assessment: The Instrument Development and Application Review - Chen, Nan; Shi, Bing; Huang, Hanyao (Frontiers in Surgery, 2022)
Objective For the patient-reported outcome (PRO) measures related to patients with velopharyngeal inadequacy (VPI), different quality of life (QOL) instruments have been developed. The present systematic review was designated to identify current VPI-related QOL instrument development, validation, and applicability. Methods Pubmed, Cochrane, Embase, Web of Science, and EBSCO databases were searched in January 2022. “Velopharyngeal” or “palatopharyngeal” and “quality of life” or “life quality” were searched in title, abstract, and keywords. This study followed Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines. Two investigators independently reviewed abstracts and full texts of the identified literature. An established checklist was used to evaluate the measurement properties of each identified instrument. Results A total of 375 articles and 13 instruments were identified, which can be divided into nine types of families according to their development procedures. Developmental and measurement characteristics, evidence of conceptual model, content validity, reliability, construct validity, scoring, interpretation, respondent burden, and presentation for all instruments were shown. Conclusion The patient's self-report assessment and parent-proxy assessment are both valuable. The conclusion that any QOL instrument is absolutely the best for patients with velopharyngeal inadequacy could not be drawn. Understanding the development and characteristics of different QOL instruments, including their reliability, validity, aim, target, language, and resource, should be important before application in clinic or research.